Comparison of Altman, Springate, Zmijewski and Grover Models in Predicting Financial Distress on Companies of Jakarta Islamic Index (JII) on 2013-2017 - Ditasari, Rollis Ayu; Triyono, T; Sasongko, Noer (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
This study aims to determine whether there are differences in the classification between the Altman,Springate, Zmijewski, and Grover models in predicting Financial Distress. The sample in this study is 15 companies incorporated in the Jakarta Islamic Index (JII) with used purposive sampling method. The data analysis techniques used non-parametric statistical tests namely Kruskal Wallis test. The Result of this study is the Difference Classification of Financial Distress between the Altman Models with Springate Models, Altman Models with Grover Models, Altman Models with Zmijewski Models, Springate Models with Grover Models, Springate Models with Zmijewski Models and No Difference in Financial Distress Classification between the Grover Models and the Zmijewski Models. Those could be seen from the results of the Ha6 statistical test which showed the value of sig. 0.156 ≥ 0.05.